THE MUNICIPAL PUBLIC ADMINISTRATION OF THE FOOD AND NUTRITION SECURITY SYSTEM IN BRAZIL - Santos, Williany Isis; Voci, Silvia Maria; Matamoros, Sara Eloísa Del Castillo Matamoros; Gabriel, Cristine Garcia; Santos, Adriana Correia dos; Pinto, Fabian Gilberto Ardila; Fagundes, Andhressa Araujo (Revista Brasileira de Gestão e Desenvolvimento Regional, 2024)
The study seeks to identify the challenges and potential of municipal public administration for the implementation of the Sistema Nacional de Segurança Alimentar e Nutricional (SISAN, National Food and Nutrition Security System) in a state in the northeastern region of Brazil. Of observational character and cross-sectional, the study used the triangulation of methods to analyze qualitative and quantitative data. With 46 representatives of the municipal public administration within the state, the analyses identified a high percentage of municipalities that did not adhere to SISAN, together with the low level of establishment of the Intersectoral Chamber of Food and Nutrition Security, preparation of the Food and Nutrition Security Plan and effective social participation mechanisms. From the perspective of the interviewees, the implementation of the system will facilitate access to resources and development at the local level, which also qualify the local indicators. However, the lack of technical support at the state and federal levels for training administrators, financial resources, as well as some vulnerabilities in the articulation of actions were perceived as difficulties for implementation, along with bureaucracy in the adhesion process and lack of interest by public administrators. We conclude that, for the implementation of SISAN, adequate government practices that promote the autonomy of the municipalities are needed, as well as encouragement and support for permanent training processes focused on local public administrators.